Foundations of Aural Skills - Chenette, Timothy (Open textbook library., 2022)
Foundations of Aural Skills is a research-based, accessible, relevant, creative, inclusive, empowering textbook for teaching introductory aural skills. The first seven chapters provide thorough instruction in aural fundamentals, allowing students to build their foundations from a variety of starting points. The following chapters address the traditional tasks of sight-reading and dictation, but also improvisation, mimicking music you hear (“playback”), transcription, and ensemble skills. The final two chapters add some basic form- and chord-listening skills. Every section includes creative activities that learners can try out on their own or do in class. Embedded playlists for practicing listening skills include a diverse range of music that will connect with students’ preferences and allow them to experience music they haven’t worked with before. While the text is primarily designed for a first semester or year of instruction, it also includes some instruction on modulation, chromaticism, and mixed meter, and future additions/development will make these advanced applications more robust.